2012
DOI: 10.1074/jbc.m112.423905
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Microtubules and Their Dynamics in Cell Migration

Abstract: Background: Microtubule effects on cell migration are poorly understood. Results: Tubulin mutations or drug treatments that suppress microtubule dynamics impede cell locomotion. Depolymerizing microtubules does not inhibit movement, but it becomes random. Conclusion: Microtubules act to restrain cell movement and specify directionality. Significance: Drugs have dose-dependent effects on microtubule behavior, cell migration, and mitosis. Understanding these actions will lead to more effective drug use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
86
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(94 citation statements)
references
References 38 publications
6
86
1
1
Order By: Relevance
“…These findings led us to conclude that fisetin is indeed a microtubule interfering agent that suppresses the microtubules which in turn led to reduction in cell migration. A parallel conclusion was previously reported that low drug concentrations in various cell lines do not affect mitosis yet inhibit motility [29], as well as by experiments showing that inhibition of cell migration by antimitotic drugs is due to their suppression of microtubule dynamics rather than to some other drug effects [30,31]. …”
Section: Discussionsupporting
confidence: 79%
“…These findings led us to conclude that fisetin is indeed a microtubule interfering agent that suppresses the microtubules which in turn led to reduction in cell migration. A parallel conclusion was previously reported that low drug concentrations in various cell lines do not affect mitosis yet inhibit motility [29], as well as by experiments showing that inhibition of cell migration by antimitotic drugs is due to their suppression of microtubule dynamics rather than to some other drug effects [30,31]. …”
Section: Discussionsupporting
confidence: 79%
“…These data further reinforce the role of Rab7a in migration and explain previous data indicating that Rab7a depletion causes a decrease, but not a complete inhibition, of vimentin phosphorylation at various sites accompanied by an increase of insoluble (filamentous) vimentin [17]. In support of this, it has been previously demonstrated that alterations of cytoskeleton components dynamics affect cell migration [75]. Notably, Rac1 and vimentin functions are connected [51][52][53][54].…”
Section: Discussionsupporting
confidence: 77%
“…On 2D surfaces, we would expect similar oscillations around the cell perimeter upon the disassembly of microtubules. However, the lack of synchronization of oscillations around the perimeter would cause the cell as a whole to undergo only short-range random walks, as reported in the literature (56,57). We would expect similar oscillations for cells migrating in confined 3D environments such as narrow channels.…”
Section: Discussionmentioning
confidence: 70%
“…Taxol-stabilized microtubules may also be defective in their interactions with other structures such as focal adhesions to affect the production of excitation and/or inhibitory signals. In addition, although nocodazole allows an anterior end to turn into a retracting posterior end during oscillation, Taxolinduced stabilization of microtubules has been shown to block cell retraction (57), which may be sufficient to prevent oscillatory migration.…”
Section: Discussionmentioning
confidence: 99%